2022
DOI: 10.5219/1711
|View full text |Cite
|
Sign up to set email alerts
|

The intensification of dehydration process of pectin-containing raw materials

Abstract: The process of intensifying dehydration of pectin-containing raw materials by using centrifugation with simultaneous application of low-frequency oscillations to the working container creates an electroosmotic effect in unilateral diffusion to improve the filtration process. It is established that to reduce the technological resistance in the presented methods; it is necessary to create a fluidized bed of products due to the oscillating motion of the working capacity. An experimental vibration unit has been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Amado D. with co-authors [25] and scientists [26] studied the nutritional and biological value of avocado peel and seeds and found that they can be used in the food, cosmetic [27], and pharmaceutical industries [28], [29]. It was determined that avocado seeds are rich in polysaccharides, proteins, lipids, vitamins, minerals, and other bioactive substances [30]. The work [31] summarises and analyses research on the main metabolites of avocado and its antioxidant and pharmacokinetic properties.…”
Section: Resultsmentioning
confidence: 99%
“…Amado D. with co-authors [25] and scientists [26] studied the nutritional and biological value of avocado peel and seeds and found that they can be used in the food, cosmetic [27], and pharmaceutical industries [28], [29]. It was determined that avocado seeds are rich in polysaccharides, proteins, lipids, vitamins, minerals, and other bioactive substances [30]. The work [31] summarises and analyses research on the main metabolites of avocado and its antioxidant and pharmacokinetic properties.…”
Section: Resultsmentioning
confidence: 99%
“…As the firing temperature increases, lime recrystallization processes take place, after which the sintering process begins. The latter interferes with the access of water to CaO particles during quenching, and lime, remaining chemically free, becomes inactive for reaction with water [12], [27].…”
Section: Resultsmentioning
confidence: 99%
“…Fat tissue in cattle carcasses plays an important role [33], [34]. Its low content worsens the taste of beef.…”
Section: Resultsmentioning
confidence: 99%